Knowledge, attitude and practices (KAP) regarding voluntary non-remunerated blood donation (VNRBD) among the students of colleges of Jammu, India - Kumari, Sonam; Raina, Tilak R. (International Journal Of Community Medicine And Public Health, 2017)
Background:A voluntary non-remunerated blood donor forms the firm foundation of blood transfusion services of a country. The healthy, active and receptive student population can be potential blood donor to meet the safe blood requirements. The objective of this study was to find out the prevalence of blood donors and to explore the Knowledge, Attitude and Practices (KAP) of the college students of Jammu, India regarding Voluntary Non-Remunerated Blood Donation (VNRBD). Methods:A descriptive study was conducted over a period of one year. It involved students of six colleges. A structured donor questionnaire regarding KAP on VNRBD was distributed among the college students. Results:1520 college students with 880 females and 640 males were involved in the study. Out of which 210 were blood donors. Prevalence of blood donors was 13.81%. In this study 81.57 % of students were aware of Voluntary Blood Donation (VBD). 62.5% of the students had awareness regarding spread and transmission of HIV/AIDS. 49.34% students were not aware of the fact that paid / professional blood donation has been banned in India. 76.68% of the students had knowledge that blood donation has medical benefits. The commonest reason for blood donation was sense of social responsibility and for not donating blood was fear of illness. 90.13% of the students were willing to donate blood in future. Conclusions:To increase the prevalence of voluntary blood donation, specific campaigns involving interactive awareness sessions on blood donation should be organized, targeting the youth, motivating them to become regular voluntary blood donors should be conducted. Barriers to blood donation especially by women should be studied and evaluated. Efforts must be undertaken to bring the knowledge and positive attitude towards VBD into application in future to achieve the goal of 100% VNRBD.